KESEIMBANGAN KEHANGATAN DAN KONTROL, ORANG TUA MENENTUKAN KONSEP DIRI DAN MOTIVASI BERPRESTASI ATLET MUDA DI SEKOLAH BERASRAMA - Rahmaisya, Rusni; Latifah, Melly; Alfiasari, Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2011)
Self-concept and sport achievement motivation are psychological factors that important for young athlete. Parenting practices in family has significant role to form self-concept and achievement motivation. This study aimed to analyze the connectedness between perception of parenting style, self-concept, and achievement motivation of young athletes. This study used cross sectional design and involved 84 students of grade tenth, eleventh, and twelfth of Sports School in Jakarta. Data analysis used descriptive analysis and correlation test. Result showed that family income had possitive significant correlation with scores of authoritarian parenting style. Scores of authoritative parenting style had possitive significant correlation with self-concept and achievement motivation of young athletes. Moreover, self-concept of young athletes; especially in aspects of athletic competences, behavior/morality, acceptance of peer group, and future image correlated significant and positive with achivement motivation of young athletes.